1989
DOI: 10.1111/j.1365-2265.1989.tb01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell Population Kinetics in Dog and Human Adult Thyroid

Abstract: Cell population kinetics was studied by bromodeoxyuridine (BrdU) histochemical and 3H thymidine radioautographic labelling in dog thyroids. In-vivo labelling with BrdU and in-vitro labelling of incubated slices with 3H thymidine gave similar results. This validates the use of in-vitro labelling of slices for the study of cell kinetics in the thyroid. In-vitro labelling of human thyroid slices demonstrated a labelling index of 13.4 x 10(-5) for follicular cells; assuming an S phase of 10 h, this corresponds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 9 publications
1
77
0
Order By: Relevance
“…Certain unregulated growth signals associated with malignant transformation may contribute to the loss of differentiated thyroid function. The thyroid cell turns over, on average, no more than five times through adulthood (25). Turnover increases in early infancy and adolescence (25,26).…”
Section: Cell Biology Of Thyroid Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Certain unregulated growth signals associated with malignant transformation may contribute to the loss of differentiated thyroid function. The thyroid cell turns over, on average, no more than five times through adulthood (25). Turnover increases in early infancy and adolescence (25,26).…”
Section: Cell Biology Of Thyroid Carcinogenesismentioning
confidence: 99%
“…The thyroid cell turns over, on average, no more than five times through adulthood (25). Turnover increases in early infancy and adolescence (25,26). Because of the homogeneity of the growth potential of follicular cells (27), a fraction of these follicular cells in adults would likely turnover much more than five times.…”
Section: Cell Biology Of Thyroid Carcinogenesismentioning
confidence: 99%
“…8,16 It has been suggested that follicle regeneration is maintained by a pool of SCs that reside in the adult gland. ASCs, estimated to be~0.1% of all thyroid cells, are undifferentiated in a quiescent or slow-cycling state and could replicate themselves to Figure 2.…”
Section: Normal Thyroid Stem Cellsmentioning
confidence: 99%
“…13,14 However, this model is not in accordance with the rare occurrence of RET/PTC and PAX8/PPARG rearrangements in ATC 15 and the low turnover rate of thyroid follicular cells (about five renewals per lifetime) that reduces the possibility of accumulating the mutations needed for transformation. 8,[16][17][18] The existence of several differentiation degrees has led to the assumption that TC cells are derived from remnants of fetal thyroid cells, such as stem cells (SCs) or precursors, rather than mature follicular cells. 9,19,20 According to this fetal cell carcinogenesis model supported by gene expression profiling data, ATC arises from fetal thyroid SCs, marked by the onco-fetal fibronectin expression and lack of differentiation markers.…”
Section: Introductionmentioning
confidence: 99%
“…The thyroid gland is capable of regenerating itself, at least to some extent, which is thought to be facilitated by stem or progenitor cells present inside the adult gland located in a niche designated as solid cell nests (Coclet et al 1989, Gibelli et al 2009). Thyroid stem cells are characterized by the expression of p63, Oct-4, hNanog, CD44 and SCA-1 and are able to differentiate into fully functional thyroid follicular cells (Hoshi et al 2007, Lan et al 2007, Klonisch et al 2009, Ahn et al 2014.…”
Section: Cscsmentioning
confidence: 99%